Análise, medidas e avaliação de desempenho de uma rede PLC em ambiente indoor de casas populares - Zattar, Haroldo Benedito Tadeu (2011)
This thesis is aimed to show the analysis, measurement and evaluation performance of the indoor power line communication (PLC) network operating at popular houses. For the PLC channel the analysis was made of the attenuation considering the parameters condition of the transmitter, receiver and load. Considering the transfer of date through power line, this work shows the results of noise signal from household appliance and the effects caused by the appliances in the PLC network. The measurements show that popular houses are able to receive signal by PLC system.